Impact of Prehospital Mobile Intensive Care Unit Intervention on Mortality of Septic Patients. Issue 1 (2018) - Jouffroy, Romain; Saade, Anastasia; Philippe, Pascal; Carli, Pierre; Vivien, Benoît
No abstract available